Entomotoxic Activity of Prasiola crispa (Antarctic Algae) in Nauphoeta cinerea Cockroaches: Identification of Main Steroidal Compounds - Holken Lorensi, Graziela (Mar Drugs, 2019)
Prasiola crispa is a macroscopic green algae found in abundance in Antarctica ice free areas. Prasiola crispan-hexaneextract (HPC) induced insecticidal activity in Nauphoeta cinerea cockroaches after 24 h of exposure. The chemical analysis of HPC revealed the presence of the followingphytosterols: β-sitosterol, campesterol and stigmasterol. The incubation of cockroach semi-isolated heart preparations with HPC caused a significant negative chronotropic activity in the heartbeats. HPC affected the insect neuromuscular function by inducing a complete inhibition of the cockroach leg-muscle twitch tension. When the isolated phytosterols were injected at in vivo cockroach neuromuscular preparations, there was a progressive inhibition of muscle twitches on the following order of potency: β-sitosterol > campesterol > stigmasterol. HPC also provoked significant behavioral alterations, characterized by the increase or decrease of cockroach grooming activity, depending on the dose assayed. Altogether, the results presented here corroborate the insecticide potential of Prasiola crispa Antarctic algae. They also revealed the presence of phytosterols and the involvement of these steroidal compounds in the entomotoxic activity of the algae, potentially by modulating octopaminergic-cholinergic pathways. Further phytochemical-combined bioguided analysis of the HPC will unveil novel bioactive compounds that might be an accessory to the insecticide activity of the algae.